Bone marrow endothelial cells sustain a tumor-specific CD8+ T cell subset with suppressive function in myeloma patients. (2nd January 2019) - Leone, Patrizia; Di Lernia, Giuseppe; Solimando, Antonio Giovanni; Cicco, Sebastiano; Saltarella, Ilaria; Lamanuzzi, Aurelia; Ria, Roberto; Frassanito, Maria Antonia; Ponzoni, Maurilio; Ditonno, Paolo; Dammacco, Franco; Racanelli, Vito; et al.
ABSTRACT: Endothelial cells (EC) line the bone marrow microvasculature and are in close contact with CD8 + T cells that come and go across the permeable capillaries. Because of these intimate interactions, we investigated the capacity of EC to act as antigen-presenting cells (APC) and modulate CD8 + T cell activation and proliferation in bone marrow of patients with multiple myeloma (MM) and monoclonal gammopathy of undetermined significance. We found that EC from MM patients show a phenotype of semi-professional APC given that they express low levels of the co-stimulatory molecules CD40, CD80 and CD86, and of the inducible co-stimulator ligand (ICOSL). In addition, they do not undergo the strong switch from immunoproteasome to standard proteasome subunit expression which is typical of mature professional APC such as dendritic cells. EC can trap and present antigen to CD8 + T cells, stimulating a central memory CD8 + T cell population that expresses Foxp3 and produces high amounts of IL-10 and TGF-β. Another CD8 + T cell population is stimulated by professional APC, produces IFN-γ, and exerts antitumor activity. Thus, two distinct CD8 + T cell populations coexist in the bone marrow of MM patients: the first population is sustained by EC, expresses Foxp3, produces IL-10 and TGF-β, and exerts pro-tumor activity by negatively regulating the second population. This study adds new insight into the role that EC play in MM biology and describes an additional immune regulatory mechanism that inhibits the development of antitumor immunity and may impair the success of cancer immunotherapy.